School leadership for democratic education in South Africa : perspectives, achievements and future challenges post-Apartheid - Makoelle, Tsediso Michael; Makhalemele, T. J.; Du Plessis, Pierre, 1978- (London : Routledge, 2022)
School Leadership for Democratic Education in South Africa explores the democratization and modernization of education in South Africa, analyzing the state of school leadership in South African schools from the time of the new democratic education dispensation in 1994 to the present day. The book maps out what the future of education in South Africa could look like and explores the most conducive educational environments for change in South African schools. It adopts a critical approach to analyzing leadership and management in the context of school governance, school effectiveness, teacher development, multiculturalism and equity in education. Contributions explore the democratization and modernization of education in South Africa through examining different perspectives, achievements and challenges, and also consider issues around access to technology, language policy and the curriculum along with new literature on selected aspects of leadership. This book will be of great interest for researchers, scholars, and students in the fields of educational leadership, sociology of education, and teacher education.
Keywords: Educational leadership -- South Africa -- History; School management and organization -- South Africa -- History; EDUCATION / Leadership; EDUCATION / Educational Policy & Reform / General; EDUCATION / Administration / General